Agrippina the Younger: Between Ambition and political Conspiracies in Rome during the First Century AD (Al-Farooq Journal of Sciences, 2026)
This study presents an analytical examination of "Agrippina the Younger" and her pivotal political roles in the history of the Roman Empire during the first century AD. The core problem of this study focuses on analyzing the mechanisms and strategies that enabled a woman in roman society to transcend traditional roles to reach the pinnacle of politidal power. Utilizing a descriptive and critical analytical methodology, the study examines classical sources while balancing them with modern scholarly perspectives. The findings of this study indicate that Agrippina's ambition was a reflection of Juio-Claudian dynasty, where she skillfully utilized family alliances as strategic tools, ultimately leading to a tragic confrontation that shifted the course of the Empire.
Keywords: Agrippina the Younger , Roman Empire, Julio- Claudian Dynasty, political participation of women, Dynastic Alliances